Women Leadership Pattern towards the Resilience of Pesantren in the TUNA Era - Moh. Hanif Adzhar; Umil Mu’alimatun Muzaroh Fitroroh; Diki Darmawan; Nabila Husna (Journal of Pesantren and Diniyah Studies, 2026)
Pesantren face new challenges in the form of turbulent, uncertain, and novel changes, or the TUNA Era, which refers to an institutional condition characterized by turbulence, uncertainty, novelty, and ambiguity. This study aims to analyze how the leadership of Nyai Hj. Bariroh Aziz at the Al-Madienah Denanyar Pesantren in Jombang builds institutional resilience through the perspectives of self-agency and feminist ethics. This study employs a qualitative case study design. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed thematically through data reduction, coding, and case interpretation. The results indicate that Nyai’s leadership is built upon eight dimensions of self-agency: self-reflection, open communication, processing of experiences, the ability to make sound decisions, analysis of long-term benefits, care for oneself and the environment, consistent commitment, and a willingness to engage in continuous learning. These dimensions form a leadership style that is reflective, adaptive, inclusive, and oriented toward the common good, thereby strengthening the resilience of the pesantren without compromising its core values. This study expands the discourse on women’s leadership in pesantrens by demonstrating that women’s agency serves as a source of institutional resilience. Theoretically, self-agency and feminist ethics help explain how the authority, moral responsibility, and strategic decisions of female leaders contribute to institutional resilience amid uncertainty.